Studying the mechanism of graphene formation by chemical vapor deposition synthesis - Shaikenova, A.; Beisenov, R.; Muratov, D. (Publishing House of the KarSU named after academician E.A.Buketov, 2018)
Due to their unique properties, 2D materials have a great potential in various applications. It argued that chemical vapor deposition (CVD) method is widely used in the synthesis of graphene. In this paper the experiments results of the synthesis of graphene layers by Chemical Vapor Deposition (CVD) method on the copper (Cu) foil discussed. However, desired quality of graphene layers is not always achievable. Therefore, controllable synthesis in domain size and morphology is required for large-scale applications. Examples of the synthesis parameters of polycrystalline and monocrystalline graphene are given. Mechanism of graphene formation studied during the synthesis process. The sample preparation processes and the main growth mechanisms of multilayer and single-layer graphene by the CVD method discussed. Obtained CVD graphene layers characterized by Raman, AFM and SEM analysis.
Keywords: two-dimensional materials; synthesis; CVD; graphene